Fa’āliyyah Istikhdām Kahoot fī Ta’līm Mahārah al-Istimā’ ‘an Bu’d Ladā Talāmīdh Madrasah Ruḥamā’ al-Mutawassiṭah al-Islāmiyyah Tanggerang - Muslimin, Muhamad Ihwanul; Nurrasyid, Hadi; Ridlo, Ubaid (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This research/paper aims to reveal the results of the tests that use the Kahoot App for the students and do not use it, and to reveal the effectiveness of the Kahoot method in teaching he remote listening skill. This research followed a semi-experimental study based on the quantitative approach, and its design consisted of the experimental group and the control group. The researcher used data collection methods, which are direct observation, personal interview, tests and questionnaires. After the researcher analyzed the data, reached the mean of the two tests, the pre-test and the post-test. Based on the average results of the experimental group at a value of 28.75 and the average results of the control group at a value of 16.75, it indicates that the average results of the experimental group are greater than the average results of the control group. And I came to the analysis of the data using the